LONG-STANDING NARRATIVE OF INDONESIAN ISLAMIC WOMEN IN FOUR NOVELS BY HABIBURRAHMAN EL SHIRAZY - Azhari, Dian Rizky; Yoesoef, M.; Setyani, Turita Indah (UI Scholars Hub, 2023)
Discussions about Islamic women have been buzzing in Indonesia after the collapse of the New Order. Its presence directly contradicts the narratives of women that were influenced by western thought, such as liberalism and secularism, as well as by global islamization movement from the Middle East. The conflicts that arose were about the role of women in the public sphere, women's independence, women's bodies and sexuality. This study aims to find similarities between ideas about Islamic women and the practice of Islamic women's discourse in Indonesian society. This study uses an intrinsic study method and a sociology of literature approach to reveal the relationship of the text to social conditions in society. The result shows that the depiction of Islamic women in the four texts is the same as the practice of Islamic women's discourse that existed in Islamic societies even before Indonesia's independence. It is considered as a writing-back movement by Habiburrahman El Shirazy to propagate the majority version of Islamic values in Indonesia.